The restoration of an urban still water fishery: monitoring for success at Tom Thumb Lake - Hughes, Stephen (Cranfield University, 2008)
Tom Thumb Lake is a former gravel pit and carp fishery situated in East London. In 2005 the Lake was restored as an accessible, self-sustaining fishery. The objectives of this study were to outline a monitoring plan to assess the success of the restoration, this included: monitoring water quality in relation to the requirements of fish, monitoring the macroinvertebrate communities in areas of the lake that will be newly vegetated, an angler survey to assess basic demographics (such as age, sex, ethnicity) and whether or not the priority groups identified by the Environment Agency were using the Lake. In addition, a basic topographic survey was conducted. Basic water quality parameters (temperature, pH, DO, N and P) were monitored at Impact sites (those to be vegetated) and Reference sites (an area of the Lake already well vegetated), macroinvertebrate samples were also taken at these locations. The water quality requirements of fish were based on Incipient Lethal Levels (ILL) taken from fish physiology publications. The survey was completed and handed out to anglers but numbers returned were not sufficient for inclusion in this report. The topographic survey identified a depth range of 0-2.4m, with shallow areas predominantly close to known gravel bars in the centre of the lake. Based on the monitoring data collected, water quality was generally well within the limits researched from literature, although temperature and pH were occasionally close to the upper limits. Macroinvertebrate samples showed some differences, particularly in total abundance, between the Impact and Reference sites. An outline set of monitoring guidelines were constructed for future managers of the Lake to follow, which should enable them to reliably gauge the success of the project. Recommendations for refining the ILL method and potential uses for other lakes were made.
Keywords: gravel pit; Environment Agency; water quality; shallow areas; Macroinvertebrate samples; carp fishery